A preliminary study on improving surface finish of electron beam melted Ti-6Al-4V using piezo vibration striking treatment. (September 2022) - Chen, Jisheng; Xu, Yang; Kwon, Patrick; Guo, Yang
Abstract: This paper presents an experimental study on surface finish improvement for electron beam melted Ti-6Al-4V using piezo vibration striking treatment (PVST), a novel mechanical surface treatment process realized by a non-resonant piezo stack vibration device installed on a CNC machine. Various experiments with different process parameters, i.e., engagement distance, tool diameter, vibration frequency, and driving voltage, are performed to explore their effects on surface finish of the additively manufactured parts. The results reveal that surface texture after PVST can be divided into two patterns: scattered pattern consisting of scattered treated and untreated areas and uniform pattern with uniform treated areas covered throughout the surface. The compression-type and sliding-type deformation under negative engagement distance between the striking tool and workpiece surface plays an important role in enhancing the surface finish and transforming surface texture from scattered pattern to uniform pattern. Tool diameter, controlling contact area between the tool and the workpiece, is positively correlated with surface finish while driving voltage, controlling vibration amplitude of the tool, is negatively correlated with surface finish. Overlap of indentations controlled by vibration frequency and scan speed has little influence on the surface finish.